Comparative evaluation of MALDI-ToF mass spectrometry and Sanger sequencing of the 16S, hsp65, and rpoB genes for non tuberculous mycobacteria species identification - Rodriguez-Pazmiño, Angel Sebastian; Carvajal, Elsy; Paredes-Núñez, Darwin; Echeverría, Jose; Calderon, Joselyn; Orlando, Solon Alberto; Parra Vera, Henry; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2025)
Non tuberculous mycobacteria (NTM) infections are increasing globally, underscoring the critical importance of accurate species-level identification for effective clinical management. This study aimed to evaluate the use of three conserved markers in the mycobacterial family (16S, hsp65, and rpoB) for NTM identification through Sanger sequencing, comparing the results to those obtained using MALDI-ToF MS. A total of 59 clinical NTM isolates from plastic surgery patients, previously characterized by MALDI-ToF MS, were analyzed. These isolates underwent DNA extraction, PCR amplification, and Sanger sequencing. Species identification was performed through phylogenetic analyses of each marker individually and concatenated as a multi locus sequencing approach. Concordance between MALDI-ToF MS and Sanger sequencing was assessed using Cohen’s Kappa statistical analysis. Cohen’s Kappa values indicated moderate concordance of 0.46 for 16S, 0.51 for hsp65, and 0.69 for rpoB. Concatenated phylogenetic analysis yielded improved concordance values of 0.71 for (16S + hsp65), 0.76 for (16S + rpoB), 0.69 for (rpoB + hsp65), and 0.72 for (16S + hsp65 + rpoB). Our results show that NTM identification is more accurate when employing a multi locus sequencing approach. Notably, the combination of 16S + rpoB outperformed the three-marker concatenation, offering the highest concordance for species-level identification. NTM identification is challenging, and concatenated phylogenetic analysis of two or more gene fragments should be used when MALDI-ToF MS or whole genome sequencing is not available.